GOODS DELIVERY SYSTEM IN PT. LAJU MERAPI - Ageng Herminto; Don Elsyafitra, SKom Don Elsyafitra, SKom (Jurnal Sistem Informasi, 2006)
The development of increasingly sophisticated computer that is very helpful in dataprocessing still using manual systems. This is often a problem associated with theaccuracy of the data which resulted in delays in data processing.Valuable information is the information quickly and accurately. Then needed acomputerized system as a supporter. Service delivery system is designed with the aimto ease in processing data and preparing reports.